Who are judicial assistants in the Republic of Serbia? - Gojković, Stefan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Judicial assistants are important part of the judiciary of the Republic of Serbia, but impression is that the public is insufficiently informed about their existence and significance. More precisely, part of the public knows that judicial assistants exist, but doesn’t know what their job is. The aim of this article is to analyze and present the position, importance, jobs, and problems of judicial assistants and to recommend some suggestions how to improve the position of this important judicial profession. It is often said that judicial assistants are the future of the judiciary, but it is mostly thought that these judicial assistants will be elected as judges "tomorrow". However, it is an uncertain circumstance, that may or may not occur in the future. At the same time, there is a part of judicial assistants who have no desire at all to be elected to the position of judge. Bearing in mind the above, i would like to focus on the present time and finding an answer to the question: How to improve the position of judicial assistants „today“?